2002
DOI: 10.1097/00005373-200206000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Acute Traumatic Rupture of the Thoracic Aorta Treated with Endoluminal Stent Grafts

Abstract: Five cases of successful endograft repair of thoracic aortic rupture have been demonstrated. This should encourage future studies to determine whether endovascular repair of thoracic aortic ruptures is a safe and feasible alternative to conventional open repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 15 publications
2
49
0
6
Order By: Relevance
“…Recent reports have shown that emergency repair of thoracic aortic disease with endovascular stent-grafts is a safe, effective and less invasive treatment option with technical success rates ranging from 90 to 100% and encouraging short-and mid-term results (Table 1) [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that emergency repair of thoracic aortic disease with endovascular stent-grafts is a safe, effective and less invasive treatment option with technical success rates ranging from 90 to 100% and encouraging short-and mid-term results (Table 1) [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently we stated endovascular treatment to be a safe and efficient therapeutic option in blunt thoracic aortic trauma [33]. Several other series also showed endovascular treatment to be an efficient therapeutic option with good short-and midterm results [2,11,[7][8][9][15][16][17][19][20][21][22][23][24][25]27,36,28,32,1]. We consider interventional radiology and stent graft placement as therapeutic option for penetrating aortic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…El uso de estas técnicas en el manejo de lesiones traumáticas agudas de la aorta ha sido reportado en forma creciente, con resultados alentadores [17][18][19][20] . A nivel nacional reportamos nuestro primer caso en 2003 21 .…”
Section: Discussionunclassified